Tumour-specific fluorescence-guided surgery for pancreatic cancer using panitumumab-IRDye800CW: a phase 1 single-centre, open-label, single-arm, dose-escalation study. (August 2020) - Lu, Guolan; van den Berg, Nynke S; Martin, Brock A; Nishio, Naoki; Hart, Zachary P; van Keulen, Stan; Fakurnejad, Shayan; Chirita, Stefania U; Raymundo, Roan C; Yi, Grace; Zhou, Quan; Fisher, George A; et al.
Summary: Background: Complete surgical resection remains the primary curative option for pancreatic ductal adenocarcinoma, with positive margins in 30–70% of patients. In this study, we aimed to evaluate the use of intraoperative tumour-specific imaging to enhance a surgeon's ability to detect visually occult cancer in real time. Methods: In this single-centre, open-label, single-arm study, done in the USA, we enrolled patients who had clinically suspicious or biopsy-confirmed pancreatic ductal adenocarcinomas and were scheduled for curative surgery. Eligible patients were 19 years of age or older with a life expectancy of more than 12 weeks and a Karnofsky performance status of at least 70% or an Eastern Cooperative Oncology Group or Zubrod level of one or lower, who were scheduled to undergo curative surgery. Patients were sequentially enrolled into each dosing group and 2–5 days before surgery, patients were intravenously infused with 100 mg of unlabelled panitumumab followed by 25 mg, 50 mg, or 75 mg of the near-infrared fluorescently labelled antibody (panitumumab-IRDye800CW). The primary endpoint was to determine the optimal dose of panitumumab-IRDye800CW in identifying pancreatic ductal adenocarcinomas as measured by tumour-to-background ratio in all patients. The tumour-to-background ratio was defined as the fluorescence signal of the tumour divided by the fluorescence signal of the surrounding healthy tissue. The dose-finding part of this study has been completed. This study is registered with ClinicalTrials.gov, NCT03384238 . Findings: Between April, 2018, and July, 2019, 16 patients were screened for enrolment onto the study. Of the 16 screened patients, two (12%) patients withdrew from the study and three (19%) were not eligible; 11 (69%) patients completed the trial, all of whom were clinically diagnosed with pancreatic ductal adenocarcinoma. The mean tumour-to-background ratio of primary tumours was 3·0 (SD 0·5) in the 25 mg group, 4·0 (SD 0·6) in the 50 mg group, and 3·7 (SD 0·4) in the 75 mg group; the optimal dose was identified as 50 mg. Intraoperatively, near-infrared fluorescence imaging provided enhanced visualisation of the primary tumours, metastatic lymph nodes, and small (<2 mm) peritoneal metastasis. Intravenous administration of panitumumab-IRDye800CW at the doses of 25 mg, 50 mg, and 75 mg did not result in any grade 3 or higher adverse events. There were no serious adverse events attributed to panitumumab-IRDye800CW, although four possibly related adverse events (grade 1 and 2) were reported in four patients. Interpretation: To our knowledge, this study presents the first clinical use of panitumumab-IRDye800CW for detecting pancreatic ductal adenocarcinomas and shows that panitumumab-IRDye800CW is safe and feasible to use during pancreatic cancer surgery. Tumour-specific intraoperative imaging might have added value for treatment of patients with pancreatic ductal adenocarcinomas through improved patient selection and enhanced visualisation of surgical margins, metastatic lymph nodes, and distant metastasis. Funding: National Institutes of Health and the Netherlands Organization for Scientific Research.